More Equal than Others? Perspectives on the Principle of Equality from International and EU Law - Amoroso, Daniele; Marotti, Loris; Rossi, Pierfrancesco; Spagnolo, Andrea; Zarra, Giovanni (The Hague : T.M.C. Asser Press : Imprint: T.M.C. Asser Press, 2023)
This book analyses the principle of equality from three perspectives: public international law, private international law and EU law. It is the first book in English providing a comprehensive overview of this principle in these areas of law and showing the current trends and issues concerning its application. Its main goal is to understand whether and to what extent the principle of equality has been affirmed in public and private international law, as well as EU law, and what - if any - the common core of this principle is. The analysis carried out in this contributed volume starts from general analyses of the principle of equality in the areas of the law covered by the book and then discusses the principle in more specific areas, such as human rights law, international adjudication (including investment law) and the law of international organizations. The book is intended to become a benchmark for academics dealing with matters of equality in public international law,private international law and EU law. It will be a useful tool for practitioners too, the collected chapters being based on the relevant case law dealing with the principle of equality. Daniele Amoroso is Professor of International Law in the Department of Law of the University of Cagliari, Cagliari, Italy. Loris Marotti is Assistant Professor of International Law in the Department of Law at the Federico II University of Naples, Italy. Pierfrancesco Rossi is Postdoctoral Fellow in International Law in the Department of Law of Luiss University, Rome, Italy. Andrea Spagnolo is Professor of International Law in the Department of Law of the University of Turin, Turin, Italy. Giovanni Zarra is Professor of International Law and International Litigation in the Department of Law at the Federico II University of Naples, Italy.
Part I. General/Theoretical Aspects -- Chapter 1. Variations on the Principle of Equality in International and EU Law -- Chapter 2. Sovereign Inequality and Struggles for Equality -- Chapter 3. Equality of States and Mutual Membership in European Union Law: Contemporary Reflections -- Part II. Equality of States and International Organizations in International and EU Law -- Chapter 4. Third World Approaches to International Law (TWAIL) and Inequality in International Criminal Justice: A Critical Assessment -- Chapter 5. The Recognition of the Formal Equality of International Organizations by the Means of an International Rule of Incorporation -- Chapter 6. The "Institutionalized Inequality" of the ESM Voting System: Doubts and Perspectives after the Reform -- Part III. Inter-Individual Equality: Human Rights and Conflict of Laws Issues -- Chapter 7. The Status of Workers in EU Free Movement Law: A Difficult Balance Between Equality and Economic Integration -- Chapter 8. Equality and Heteronormativity: Heterosexual Majority and Homosexual Minority in the European Convention on Human Rights -- Chapter 9. Equality, Conflict of Laws and Human Rights -- Chapter 10. Equality in the Application of "Imperative Norms": A "More Equal than Others" Principle in EU Conflict of Laws in Contractual Matters? -- Part IV. Procedural Aspects of Equality -- Chapter 11. Equality before Courts and Tribunals - The Case for a Comparative Approach -- Chapter 12. Equality in the Access to the ECtHR - Filling Procedural Gaps Concerning Locus Standi and Representation of Extremely Vulnerable Individuals -- Chapter 13. Residual Jurisdiction in Civil and Commercial Matters through the Lens of Non-Discrimination and Reciprocity -- Chapter 14. Equality and Asymmetry in Treaty-Based Investment Arbitration: Counterclaims by Host States -- Part V Epilogue -- Chapter 15. Epilogue - Animal Farm, International Law - Lorenzo Gradoni -- Chapter 16. General Conclusions: (In)Equalities and International Law: Between Oldand New Forms.
Keywords: International law; Private international law; Conflict of laws; Comparative law; Law -- Europe; Human rights; Mediation; Dispute resolution (Law).; Arbitration (Administrative law).; International criminal law; Public International Law; Private International Law, International and Foreign Law, Comparative Law; European Law; Human Rights; Dispute Resolution, Mediation, Arbitration; International Criminal Law